2017
DOI: 10.1111/jpc.13436
|View full text |Cite
|
Sign up to set email alerts
|

Controlled trial of Hartmann's solution versus 0.9% saline for diabetic ketoacidosis

Abstract: HS is an acceptable alternative to NS in DKA and may benefit those with severe DKA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
71
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(78 citation statements)
references
References 14 publications
4
71
0
3
Order By: Relevance
“…[15][16][17]30 Consistent with our results, each of these trials found point estimates favoring faster DKA resolution with balanced crystalloids, although small sample sizes led to low power. [15][16][17]30 Mahler et al 15 randomized 45 adults with DKA and found Plasma-Lyte A led to higher plasma bicarbonate concentrations than saline after 24 hours (20 vs 17 mmol/L; P = .02). Van Zyl et al randomized 54 adults with DKA and found the median time to reach a pH greater than or equal to 7.32 was 540 minutes with lactated Ringer's and 683 minutes with saline (P = .25).…”
Section: Balanced Salinesupporting
confidence: 84%
See 1 more Smart Citation
“…[15][16][17]30 Consistent with our results, each of these trials found point estimates favoring faster DKA resolution with balanced crystalloids, although small sample sizes led to low power. [15][16][17]30 Mahler et al 15 randomized 45 adults with DKA and found Plasma-Lyte A led to higher plasma bicarbonate concentrations than saline after 24 hours (20 vs 17 mmol/L; P = .02). Van Zyl et al randomized 54 adults with DKA and found the median time to reach a pH greater than or equal to 7.32 was 540 minutes with lactated Ringer's and 683 minutes with saline (P = .25).…”
Section: Balanced Salinesupporting
confidence: 84%
“…Van Zyl et al randomized 54 adults with DKA and found the median time to reach a pH greater than or equal to 7.32 was 540 minutes with lactated Ringer's and 683 minutes with saline (P = .25). Yung et al 17 randomized 77 children with DKA and found the geometric mean time to plasma bicarbonate concentration greater…”
Section: Balanced Salinementioning
confidence: 99%
“…Subsequent fluid management (deficit replacement) can be accomplished with 0.45% to 0.9% saline or a balanced salt solution (Ringer's lactate, Hartmann's solution or Plasmalyte) Fluid therapy should begin with deficit replacement plus maintenance fluid requirements. All children will experience a decrease in vascular volume when plasma glucose concentrations fall during treatment; therefore, it is essential to ensure that they receive sufficient fluid and salt to maintain adequate tissue perfusion. Deficit replacement should be with a solution that has a tonicity in the range 0.45% to 0.9% saline, with added potassium chloride, potassium phosphate or potassium acetate (see below under potassium replacement) .…”
Section: Clinical and Biochemical Monitoringmentioning
confidence: 99%
“…Subsequent fluid management (deficit replacement) can be accomplished with 0.45% to 0.9% saline or a balanced salt solution (Ringer's lactate, Hartmann's solution or Plasmalyte). 95,100,[108][109][110][111][112][113][114] • Fluid therapy should begin with deficit replacement plus maintenance fluid requirements.…”
Section: Deficit Replacement Fluidsmentioning
confidence: 99%
“…In non-critically ill children undergoing major surgery, balanced solutions have been associated with less hyperchloremia and less metabolic acidosis when compared to 0.9% saline [20]. Moreover, a randomized controlled trial (RCT) on initial IV fluid in children with DKA showed Hartmann’s solution, when compared to 0.9% saline, to be associated with shorter hospital length of stay overall and a shorter time to normalization of pH in the subgroup of severe DKA [21]. However, in pediatric acute severe diarrheal dehydration, Kartha et al showed no difference between RL and 0.9% saline in biochemical or clinical outcomes [22] while Allen et al showed more rapid improvement of serum bicarbonate and faster resolution of dehydration with RL [23].…”
Section: Introductionmentioning
confidence: 99%